2005
DOI: 10.1089/ham.2005.6.215
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Intermittent Hypoxia on Heart Rate Variability during Rest and Exercise

Abstract: Changes in heart rate variability induced by an intermittent exposure to hypoxia were evaluated in athletes unacclimatized to altitude. Twenty national elite athletes trained for 13 days at 1200 m and either lived and slept at 1200 m (live low, train low, LLTL) or between 2500 and 3000 m (live high, train low, LHTL). Subjects were investigated at 1200 m prior to and at the end of the 13-day training camp. Exposure to acute hypoxia (11.5% O(2)) during exercise resulted in a significant decrease in spectral comp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

9
37
2
4

Year Published

2008
2008
2019
2019

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 49 publications
(56 citation statements)
references
References 36 publications
9
37
2
4
Order By: Relevance
“…18 A similar behaviour for cardiorespiratory parameters has also been described for acute simulated altitude exposure. 19,20 Simulated altitude systems are now more frequently used than ''real'' high altitude exposure. In this sense there are two types of simulated altitude exposure: hypobaric hypoxia (low pressure chambers) and normobaric hypoxia (hypoxic gas mixtures).…”
Section: Introductionmentioning
confidence: 99%
“…18 A similar behaviour for cardiorespiratory parameters has also been described for acute simulated altitude exposure. 19,20 Simulated altitude systems are now more frequently used than ''real'' high altitude exposure. In this sense there are two types of simulated altitude exposure: hypobaric hypoxia (low pressure chambers) and normobaric hypoxia (hypoxic gas mixtures).…”
Section: Introductionmentioning
confidence: 99%
“…The increase in total power suggests that intermittent hypoxic increased the response of the autonomic nervous system mainly through increased sympathetic activity. Exposure to acute hypoxia during exercise resulted in a significant decrease in spectral components of HRV in comparison with exercise in normoxia [14].…”
Section: Discussionmentioning
confidence: 91%
“…Frequency domain analysis of HRV dissects sympathetic and parasympathetic activity [6,14], but it is very sensitive to data point missing [16,17]. Loss of data point is irrelevant to the calculation of Sample Entropy, the research of [18] shown that Sample Entropy little affected by loss of more than one-third of the data.…”
Section: Discussionmentioning
confidence: 99%
“…Resultado também confirmado por outros estudos (POVEA et al, 2005;ALARCÓN et al, 2012), tanto para o repouso quanto durante o exercício submáximo. A diminuição da SpO 2 e o aumento do débito cardíaco em repouso ou em exercício submáximo são considerados os fatores decisivos para a redução do VO 2MÁX em altitude (CALBET et al, 2003).…”
Section: Discussionunclassified
“…Beidleman et al, (2003) observaram que a SpO 2 de repouso aumentou de 82% para 90% e a FC diminuiu de 93 para 78 bpm após três semanas de aclimatação (4h/dia, 5 dias/semana, 4.300 m). Semelhantes tendências são relatadas em estudos com hipoxia normobárica (POVEA et al, 2005;VENTURA et al, 2003 De acordo com estudos anteriores (BENDER et al, 1989;BEIDLEMAN et al, 2003), a redução da FC de repouso reflete também na queda da FC durante exercício submáximo após aclimatação a altitude. Ambas as situações apresentam redução do débito cardíaco (GROVER; WEIL; REEVES, 1986) para a mesma intensidade de esforço, e isso implica em menor carga de trabalho ao coração.…”
Section: Discussionunclassified